Strategi Pengembangan Ekowisata sebagai Produk Pariwisata Berkelanjutan di Desa Karya Sari, Kabupaten Tabanan - Sukariyanto, I Gede Made; Susila, I Made Gede Darma (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2023)
With post-pandemic conditions becoming more conducive, tourism activities are also gradually returning to a normal position. Experience during the pandemic has changed the mindset of tourists towards tourist destinations, where in the next normal period, tourists are predicted to prefer destinations for